Develop Your Leadership Skills : fast, effective ways to become a leader people want to follow - Adair, John Eric, 1934- (New York, NY: Kogan Page Limited, 2022)
"This indispensable guide from leadership guru John Adair, will boost your confidence levels, inspire you and help you on your journey to becoming a leader of excellence. Acknowledged as a world expert, John Adair offers stimulating insights into recognizing and developing individual leadership qualities, acquiring personal authority and, most importantly, mastering core leadership functions such as planning, communicating and motivating. This 5th edition now features even more practical exercises, useful templates, and top tips to improve or develop your leadership skills, this guide distils the essence of John Adair's teaching and provides a framework for becoming an effective leader. The Creating Success series of books... Unlock vital skills, power up your performance and get ahead with the bestselling Creating Success series. Written by experts for new and aspiring managers and leaders, this million-selling collection of accessible and empowering guides will get you up to speed in no time. Packed with clever thinking, smart advice and the kind of winning techniques that really get results, you'll make fast progress, quickly reach your goals and create lasting success in your career"--
Revised edition of the author's, [2019]
Revised edition of the author's
Includes bibliographical references.
Keywords: Leadership